Job Stress Impact on Nurse's Organizational Commitment and The Role of Work Life Balance - Rezky Ariany Aras; Aulia Rezky Rahmadani; Nihar Nurkhalifa; Nurhudaeni Rahmiani (Pusat Penerbitan dan Publikasi Ilmiah, Fakultas Ekonomi dan Bisnis, Universitas Muslim Indonesia, 2022)
Work-life balance is one of the strategic issues employees face, especially for nurses who serve as essential workers in the pandemics. Maintaining the balance between family and career would affect a nurse capacity in managing stress during the covid-19 pandemics. On the other hand, work-life balance has an impact on employees' organizational commitment. This research aims to explore work-life balance's role, especially concerning employees' organizational commitment. This study observes nurses in Makassar city, Indonesia. In order to understand the impact of job stress on organizational commitment and to see the role of work-life balance, this study used mediated regression test. The result showed that work-life balance plays an essential role in mediating the relationship between job stress and organizational commitment on nurses. The direct effect of job stress with controlled work-life balance is not significant (p > 0,05). The indirect effect was at -0,2165, which is significant because it does not pass 0 on the bootstrap confidence interval. The significant indirect effect indicates that job stress influences organizational commitment due to declining work-life balance.